Pasireotide for the Medical Management of Feline Hypersomatotropism. (6th May 2015) - Scudder, C.J.; Gostelow, R.; Forcada, Y.; Schmid, H.A.; Church, D.; Niessen, S.J.M.
<x xml:space="preserve">Abstract</x> Background Feline hypersomatotropism (HST) is a cause of diabetes mellitus in cats. Pasireotide is a novel multireceptor ligand somatostatin analog that improves biochemical control of humans with HST. Hypothesis/Objectives Pasireotide improves biochemical control of HST and diabetes mellitus in cats. Animals Hypersomatotropism was diagnosed in diabetic cats with serum insulin‐like growth factor‐1 (IGF‐1) concentration >1, 000 ng/mL by radioimmunoassay and pituitary enlargement. Methods Insulin‐like growth factor 1 was measured and glycemic control assessed using a 12‐hour blood glucose curve on days 1 and 5. On days 2, 3, and 4, cats received 0.03 mg/kg pasireotide SC q12h. IGF‐1, insulin dose, and estimated insulin sensitivity (product of the area under the blood glucose curve [BGC] and insulin dose) were compared pre‐ and post treatment. Paired t‐tests or Wilcoxon signed rank tests were employed for comparison where appropriate; a linear mixed model was created to compare BGC results. Results Insulin‐like growth factor 1 decreased in all 12 cats that completed the study (median [range] day 1: 2, 000 ng/mL [1, 051–2, 000] and day 5: 1, 105 ng/mL [380–1, 727], P = .002, Wilcoxon signed rank test). Insulin dose was lower on day 5 than on day 1 (mean reduction 1.3 [0–2.7] units/kg/injection, P = .003, paired t‐test). The product of insulin dose and area under the BGC was lower on day 5 than day 1 (difference of means: 1, 912; SD, 1523; u × mg/dL × hours, P = .001; paired t‐test). No clinically relevant adverse effects were encountered. Conclusions Short‐acting pasireotide rapidly decreased IGF‐1 in cats with HST and insulin‐dependent diabetes. The decrease in IGF‐1 was associated with increased insulin sensitivity.